New chromosome reports in the subtribes Diocleinae and Glycininae (Phaseoleae: Papilionoideae: Fabaceae) - Espert, S.M. (2008)
The base chromosome number of x = 11 is the most probable in all the subtribes included in tribe Phaseoleae, although some aneuploid reduction is evident in Collaea and Galactia (Diocleinae) and chromosome duplications are seen in Amphicarpaea, Cologania and Glycine (Glycininae). The aims of this study were to improve the cytological knowledge of some species of Collaea and Galactia and to examine the anomalous counts reported for Calopogonium (Glycininae) and verify its taxonomic position. In addition, a molecular phylogeny was constructed using nuclear ribosomal DNA sequences (internal transcribed spacer region), and the chromosome number was optimized on the topology. In this work, the chromosome counts for Galactia lindenii, Galactia decumbens and Collaea cipoensis (all 2n = 20), and Calopogonium sericeum (2n = 22) are reported for the first time. The new reports for Galactia and Collaea species are in agreement with the chromosome number proposed for subtribe Diocleinae. The study rejects the concept of a cytologically anomalous Calopogonium and, based on the phylogenetic analysis, corroborates the position of this genus within subtribe Glycininae. The ancestral basic chromosome number of x = 11 proposed for Phaseoleae is in agreement with the evolutionary pathway of chromosome numbers analysed in this work. © 2008 The Linnean Society of London.